PENGARUH PENAMBAHAN TEPUNG RUMPUT LAUT EUCHEUMA COTTONII TERHADAP PEMBUATAN MASKER WAJAH - Maruka, Safriyanto S; Nurfadilah, Nurfadilah (Sekolah Tinggi Perikanan dan Kelautan (STPL) Palu, 2020)
Face masks are cosmetics that used to brighten facial skin and protect against free radical damage while maintaining skin's youthfulness. Eucheuma cottonii seaweed is a seaweed that has useful content for the skin, including high antioxidant content, and could use as an essential ingredient in facial masks. The aim of this study to determine the effect of different ratios of seaweed addition to pH, time of drying, and organoleptic preparation, while the benefits of this research were as information material about the use of Eucheuma cottonii seaweed as a natural mask and IPTEK contribution to Central Sulawesi. The research carried out in August 2017 at the Basic Laboratory and the Laboratory of Applied Marine Products Processing Technology, Palu Polytechnic. This research used Randomized Group Desig for Organoleptic and Completely Randomized Design for pH and drying time, with 5 treatments each repeated 3 times, so there are 15 experimental units. The pH value of Eucheuma cottonii seaweed facial masks on each treatment showed that there was no significant difference in the pH value of 7.2 for each treatment. In contrast, for the dried treatment was the best, A5 treatment with a drying time of 20.6 minutes. The quality of Eucheuma cottonii seaweed based on each treatment that was by the applied standards, so the best concentration was on A5 treatment. The pH value, drying time, and organoleptic preparations in this study generally meet the quality standards of masks set by the Indonesian National Standards and supported by existing research results.